Simulation of the compensation of a high-current ion beam by an electron beam in a cusp magnetic system - Onishchenko, I.N.; Fedorovskaya, O.V. (Вопросы атомной науки и техники, 2021)
The results of 2.5D-simulation of the dynamics of particles of a high-current ion beam moving in a magnetic field of acute-angled geometry (cusp), compensated in charge and current by an electron beam injected along the radius onto the axis from the periphery, uniformly in azimuth, are presented. The influence of own space charge fields and polarization fields on the dynamics of ions is clarified. It is shown that at high densities of the electron and ion beams, the electron beam injected into the cusp together with the ion beam, moving along the magnetic field lines, drags the ion beam away from the axis to the periphery into the region of zero magnetic field. At the exit from the cusp, the electron beam injected along the radius onto the axis drifts along the axis in a uniform magnetic field, while the ion beam performs oscillatory motion by radius in the crossed the electric field of the electron beam space charge and the longitudinal magnetic field. Представлено результати 2,5D-чисельного моделювання динаміки частинок потужнострумового іонного пучка, що рухається в магнітному полі гострокутної геометрії (каспі), скомпенсованого за зарядом і струмом електронним пучком, інжектованим за радіусом на вісь з периферії однорідно по азимуту. З'ясовано вплив поляризаційних полів на динаміку. Показано, що при великій щільності електронного та іонного пучків електронний пучок, інжектований в касп разом з іонним пучком, рухаючись за силовими лініями магнітного поля, захоплює за собою від осі іонний пучок на периферію в область нульового магнітного поля. На виході з каспу інжектований за радіусом на вісь електронний пучок дрейфує уздовж осі в однорідному магнітному полі, тоді як іонний пучок здійснює осциляторний за радіусом рух у схрещених електричному полі просторового заряду електронного пучка і зовнішньому магнітному полі. Представлены результаты 2,5D-численного моделирования динамики частиц сильноточного ионного пучка, движущегося в магнитном поле остроугольной геометрии (каспе), скомпенсированного по заряду и току электронным пучком, инжектированным по радиусу на ось с периферии однородно по азимуту. Выяснено влияние собственных полей пространственного заряда пучков и поляризационных полей на динамику ионов. Показано, что при больших плотностях электронного и ионного пучков электронный пучок, инжектированный в касп вместе с ионным пучком, двигаясь по силовым линиям магнитного поля, увлекает за собой ионный пучок от оси на периферию в область нулевого магнитного поля. На выходе из каспа инжектированный по радиусу на ось электронный пучок дрейфует вдоль оси в однородном магнитном поле, тогда как инжектированный по оси ионный пучок совершает осцилляторное по радиусу движение в скрещенных радиальном электрическом поле пространственного заряда электронного пучка и продольном магнитном поле.